Relación entre los estilos de apego e ideación suicida en adolescentes - Alcarraz Tineo, Ruth Gabriela (2024)
Adolescence is a critical stage characterized by changes at a physical, social and psychological level. In this period, attachment is essential, as is the bond formed with parents from an early age. On the other hand, suicidal ideation is characterized by recurring thoughts about death in the face of environmental stressors and difficulties. Therefore, the present study seeks to establish the association between attachment styles and suicidal ideation in adolescents. To this end, research was collected according to the PRISMA criteria, considering the Scopus, Web of Science, Ebsco and PubMed databases, selecting ten articles. The results report a positive relationship between insecure and avoidant attachment styles and suicidal ideations. Because these people maintain a negative perception of themselves, they are vulnerable to continually experiencing negative emotions in interaction with the environment, triggering suicidal ideations. On the other hand, secure attachment maintains a negative relationship with suicidal ideations. Finally, early intervention allows us to identify and respond to the different factors that intervene in the formation of attachment and suicidal ideation in adolescents.